Seroprevalence of transfusion transmitted infections in voluntary and replacement blood donors in a tertiary care hospital blood bank of Anantapur, Andhra Pradesh, India: 5 years retrospective study - Naik, V. Siva Sankara; M., Neeraja; R., Sujeeva Swapna; C., Bhavani; P., Sravani; T. C. S., Suman Kumar (International Journal of Research in Medical Sciences, 2020)
Background: Critical part of transfusion is effective screening of TTI, to reduce the risk of transmission is as safe as possible. The present study has undertaken to focus on seroprevalence of TTIs among both voluntary and replacement donors and also to project epidemiological data of TTIs in this community. Methods: This is a retrospective study conducted from January 2014 to December 2018. All blood samples collected from donors were screened for HIV, HBV, HCV, Syphilis and malaria according to blood bank policy. Before drawing blood, donors were asked to fill pre structured Blood bank questionnaire and consent form. Results: In this present 5-year study, total number of blood donor population was 54937, among them voluntary donors were 33891 and replacement donors were 21046. Out of 33891 voluntary donors, 33486(98.8%) were males and remaining 405(1.19%) were females. All replacement donors (21046) were males. The seroprevalence of HBV was highest, 1.82% (1003/54937) followed by HCV 0.31% (175/54937) in all the donors. The seropositivity for HIV is 0.23% (129/54937), for syphilis 0.04% (24/54937) and for malaria 0.01% (6/54937). Conclusions: National blood transfusion policy should be strengthening the standards and quality of screening across the country. For blood screening, resources and appropriate screening assays must be available at all health centres.